Factors Affect Income of Traders Retailer Fresh Sea Fish in Terapung Market Tembilahan District Indragiri Hilir Riau Province - Sumardianto '; Eni Yulinda; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Study was conducted in February 2016 at Terapung market tembilahan district Indragiri Hilir Province Riau. This study aims to analyzed levels of income of traders retailers and influence capital, the quantity of fish sold and experience on the income of traders retailer fresh sea fish in Terapung market Tembilahan. Methods used in research was survey by the number of respondents about 13 people. The income traders retailer fresh sea fish in Terapung market town Tembilahan high at between Rp 59.970.000, - Rp 88.650.000, - per month for gross income and Rp 1.717.500, - Rp 5.377.500, - per month for net income. The proportion of capital variable influence, the quantity of fish and business experience simultaneously against revenue traders retailer of marine fishes of floating market by 96,9 %. Capital significant exert against revenue traders retailer worth the of 1,460 regression. While, the quantity of fish and business experience not to revenue significant traders retailer worth the regression of 0,478 and 0,026.Keywords: income, traders retailer, Terapung market, Tembilahan